Cough In Children: The Most Common Problem In Pediatrics (Eurasian Medical Research Periodical, 2024)
Cough is a common problem in childhood, which leads to frequent visits to the pediatrician, affects the quality of life, and also causes material losses for the family and society. In pediatric practice, cough is most often associated with acute respiratory infections, which can be observed in children up to 5-8 times a year. 50-70% of children under 1 year and 30-60% of school-age children consult pediatricians with this problem. When examining patients with cough, the most common causes of recurrent cough can be bronchial asthma, prolonged bacterial bronchitis, chronic ENT diseases, gastroesophageal reflux, as well as bronchial reactivity after respiratory syncytial, rhinovirus or pertussis infections. Under the influence of external factors, mucociliary clearance in children can decrease, which contributes to the development of infections. The effectiveness of cough in children, especially at an early age, depends on the severity of the cough reflex, bronchial patency, and viscosity of bronchial secretions. The choice of therapy affecting cough should take into account age characteristics and the etiology of cough. In case of prolonged cough, unjustified treatment with antibiotics leads to an increased risk of developing resistance to antibacterial drugs. Codeine-containing drugs, given their potential side effect in the form of respiratory depression and opioid toxicity, are not recommended for use in children under 12 years of age. An alternative in the treatment of cough are herbal preparations with a complex effect: anti-inflammatory, bronchodilator, expectorant and mucolytic